Tarbawi's Tafsir as a Philosophical Foundation for Islamic Education - Tatang Sholahuddin Ma'ruf; Iskandar Mirza (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
The foundations of Islamic education are the basics that are the main basis for the development of Islamic education. This includes the main sources used as guidelines in Islamic education, such as the Koran and the Sunnah of the Prophet Muhammad SAW. This foundation gives strength and firmness to Islamic education. The philosophical basis of Islamic education is the philosophical study of Islamic education which is based on the Koran, the Sunnah of the Prophet, and the thoughts of the ulama. This also includes social values that do not conflict with Islamic teachings and the legacy of ulama thought. Islamic education originates from divine teachings, and the main sources are the Koran and Sunnah. The goals of Islamic education include the development of a primary personality based on Islamic values and norms. The main goals are to strengthen faith, form noble character, develop religious, scientific knowledge and life skills, as well as understanding the afterlife. This goal directs individuals to become human beings with good morals and contribute positively to people's lives. In accordance with the verse of the Qur'an in QS.Ad-Dhariyat/51:56, the goal of a Muslim's life is to serve and fear Allah. This piety is expressed through worship and devotion to Him as the Almighty Creator